2019
DOI: 10.1128/aem.01180-19
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Mycobacterial Diversity in Soil

Abstract: Mycobacteria are a diverse bacterial group ubiquitous in many soil and aquatic environments. Members of this group have been associated with human and other animal diseases, including the nontuberculous mycobacteria (NTM), which are of growing relevance to public health worldwide. Although soils are often considered an important source of environmentally acquired NTM infections, the biodiversity and ecological preferences of soil mycobacteria remain largely unexplored across contrasting climates and ecosystem … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…Additionally, M. kansasii and M. abscessus, which are frequently isolated from clinical samples, were not isolated. The distribution of NTM species can be affected by environmental factors such as nutrients, acidity and the aridity of soil [51]. In this context, the absence of several clinically relevant NTM species in the current study might be related to the characteristics of the soil samples and sampling sites.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, M. kansasii and M. abscessus, which are frequently isolated from clinical samples, were not isolated. The distribution of NTM species can be affected by environmental factors such as nutrients, acidity and the aridity of soil [51]. In this context, the absence of several clinically relevant NTM species in the current study might be related to the characteristics of the soil samples and sampling sites.…”
Section: Discussionmentioning
confidence: 83%
“…Antibiotic resistance of NTM has been described in previous studies [54][55][56][57]. Several studies reported evidence of the transmission of NTM infection from environmental sources [51,58]. Therefore, the antibiotic resistance profile of NTM in environmental sources is key to establishing a treatment and control strategy for NTM infection.…”
Section: Discussionmentioning
confidence: 92%
“…The assessment of soil bacterial diversity has mainly relied on 16S ribosomal RNA (rRNA) gene sequencing and has indicated that the most abundant bacterial phylotypes in global soils include Alphaproteobacteria, Gammaproteobac-teria, Betaproteobacteria, Actinobacteria, Acidobacteria and Planctomycetes (Fierer et al, 2012;Delgado-Baquerizo et al, 2018). Besides the use of DNA-based techniques, lipid biomarkers offer an additional tool to investigate soil bacterial communities, such as branched glycerol dialky glycerol tetraether (brGDGTs) believed to derive from soil acidobacteria (Weijers et al, 2009;Peterse et al, 2010;Sinninghe Damsté et al, 2018) or lipids derived from methanotrophic bacteria like certain fatty acids (Bull et al, 2000;Bodelier et al, 2009), specific bacteriohopanepolyols (van Winden et al, 2012;Talbot et al, 2016) or 13 C-depleted hopanoids (Inglis et al, 2019;van Winden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The NTM species responsible for human lung infections are thought to be influenced by the specific environmental source exposures and the NTM species diversity within these environmental niches. While water-associated biofilms contain potentially disease-causing NTM, a variety of NTM species have also been discovered in soil (2)(3)(4). Prior studies have shown that potting soil can be a reservoir for clinically relevant mycobacteria (4).…”
Section: Introductionmentioning
confidence: 99%